Trends in farm labour productivity and implications for cassava industrialisation in Nigeria - Ezedinma, C.I.; Okarter, C.; Asumugha, G.N.; Nweke, F. (2006)
Nigeria is presently the largest cassava producing country in the world. Cassava production is primarily at the smallholder level relying heavily on the hoe and cutlass and driven by human physical effort. Agricultural farm labour is a critical factor as Nigeria strives to utilise cassava as an industrial crop. With increase in rural urban migration, the aging of the rural population, and the feminisation of agriculture, rural farm labour is likely to remain inelastic and expensive for agro industrial purposes. This paper isbased on panel data collected in 46 villages first by the Collaborative Study of Cassava in Africa (COSCA) in Nigeria in 1990 and the Integrated Cassava Project in 2004. The same methodology was used in the two surveys. But unlike the COSCA survey. The 2004 survey adopted GPS equipment’s for field measurements unlike the compass and tape method adopted by COSCA. The specific field activities in each village include group interviews, farmer interviews, field and yield measurements. Results indicate that the trend in the use of labour by gender and source for cassava production has not changed over the last 15 years in Nigeria. However agricultural farm labour costs and farm wages have risen significantly over the same period. Since labour costs are usually sticky downwards, rising labour costs may pose a threat to the utilisation of cassava as a raw material for industrial purposes in Nigeria. Producing cassava in the sub humid ecology of Nigeria seems to have a relatively higher comparatiile farm labour advantage while the use of improved cassava varieties reduced labour costs by 15 percent in physical and economic terms. But further input such as mechanisation and agrochemicals are required to improve technical efficiency at the farm level and reduce production costs in the cassava enterprise in Nigeria.